Controlled Synthesis of ZnO Nanorods Using Different Seed Layers. (9th December 2020) - Biehler, Erik; Whiteman, Rachel; Lin, Pengtao; Zhang, Kai; Baumgart, Helmut; Abdel-Fattah, Tarek M.
Abstract : Single-crystal, low-cost, low-temperature, hydrothermal synthesis ZnO nanorods were grown on ZnO fine grained random nanocrystalline seed layers prepared by atomic layer deposition (ALD) and benchmarked against spin coating techniques for seed layers. As the growth temperature increased to 90 °C, more nanorods were observed on the samples. Increasing the growth time from 16 h to 24 h resulted in higher nanorod density for the ALD seeded samples, but less nanorods for the spin-coated seeded samples. Our work demonstrates that the final density of ZnO nanorods and their shape and size are primarily influenced by the characteristics of the ZnO seed layer, such as composition, morphology, grain size, impurity content and thickness, as well as the time spent heated. At ∼10 nm the ALD generated random polycrystalline seed layer grains were one order of magnitude smaller compared to the spin coating generated seed layer grains which appear structurally different as ∼100 nm columnar grains. This morphological seed layer difference caused the ZnO nanorods grown on spin coated seed layers to reach only ∼34% of the average nanorod length achieved on ALD seeds with comparable rod diameter and can also account for the diminished nanorod density. The exact mechanism of how the seed layer affects nucleation and subsequent nanorod growth is unknown, but results suggest that there is a significant impact. Future research can be directed to investigating the ability of metal nanoparticles to self-assemble on these nanorods and to further nanoscale catalysis.